(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research aims at shedding light on the concept of insurance awareness and clarifying its role on marketing insurance services of a sample of (100) employees in the National Company for Insurance. Questionnaire is used as a main instrument for collecting data and information from the sample. Their answers were analyzed by using arithmetic means, standard deviation, centesimal weight, and the correlation coefficient ( , F, t) tests .The research reached several conclusions of which:1.The sample member’s response to insurance awareness and marketing insurance services factors was in the medium level.2.There was a positive relationship of a moral sign between insurance awareness and marketing insurance services, that correlation coefficient reached (0.715).3.There is an effect of moral meaning of insurance awareness in marketing insurance services, the degree is (51%).4.There are no differences of moral sings in the sample answers to show the role of insurance awareness in marketing insurance services according to personal characteristics (age, academic qualifications, number of years in service and administrative level).